Growth of solutions of fractional differential equations - Semochko, N. S.; Chyzhykov, I. E. (Reports of the National Academy of Sciences of Ukraine, 2016)
We prove the existence and uniqueness of a solution of some fractional differential equation. With the aid of the Wiman–Valiron method, the order of growth for the solution is found as well.